Organizational climate research: a tool for improving work environment - Vilas Boas, Ana Alice; Almeida, Luciana Porto de Matos; Rodrigues, Luiz Carlos; de Oliveira, José Vilmar (Revista ADMPG, 2009)
The organizational climate research is a tool used to survey satisfaction or non satisfaction factors of the individual in the organizational context. Such factors are closely connected to organizational behavior and the attitude that the company must adopt in the sense of the elaboration, implantation, and monitoring that comes to attend the employees’ expectancies regarding satisfaction factors or to minimize their anxiety in relation to the non satisfaction factors. In this sense, the X Company which adopts this tool to evaluate its organizational climate was chosen as sample for this paper. Thus, the hereunder study aims to show and analyze the data the environment research could offer and, from the results of this tool to suggest improving actions regarding the observed factors. The case study data were gathered by means of a consultant company which applied a questionnaire, adopting the Likert scale methodology. The findings showed this company is far from achieving a favorable position regarding the observed factors. There is a lot more to be done in relation to all analyzed factors, once there are data that are in dissonance with interconnected subjects. However, the organizational climate research proved to be an important tool so that the company may visualize the level of satisfaction and non satisfaction of their collaborators. It allows also the implementation of corrective actions to the factors that negatively influence the organization environment.